Making it “pay a bit better”: design challenges for micro rural enterprise - Crabtree, Andy; Chamberlain, Alan (2013)
This paper reports on a field study of small market in Wales undertaken as part of broader research project aimed at developing IT solutions to support rural enterprise. The project is predicated on the assumption that the primary challenge facing rural enterprise is that of scale and that IT solutions could and should add value by enabling growth. The study suggests that many rural enterprises are micro in character, that they are not driven by the need to grow, and that value is and can be added in different ways that reflect the social values oriented to and employed by micro businesses and their consumers. The paper elaborates vernacular understandings of supply chains and their coordination, along with business and consumer motivations to consider alternative possibilities for design that place emphasis on making micro rural enterprise ‘pay a bit better’ rather than scaling it up.